A study on quality of life among the elderly at urban health center in North Delhi - Gunjan Mahaur; Archana Dwivedi; Deepika Joshi; Nidhi Dwivedi (Wolters Kluwer Medknow Publications, 2023)
Background: Elderly population in India is growing around 3% annually and is supposed to triple by 2050 than that at the time of 2011 census, according to a country report published by the UN Population Fund (UNFPA, 2017). A better quality of life (QOL) of the elderly has become a major public health challenges of the 21st century, so timely emphasis on maintenance of physical health and psychological issues is crucial. Therefore, the aim of the present study is to measure QOL among the elderly population and to find out the association with sociodemographic factors. Materials and Methods: This is a cross-sectional study done among the elderly population of an urban health training center. The study includes the World Health Organization Quality of Life Questionnaire-Brief version and a questionnaire for sociodemographic variables. Univariate and multivariate analyses were used to determine associations and P value. Results: The overall QOL scores ranged between 52 and 110, with a mean score of 78.59 ± 12.6. Good QOL was observed among 64.9%of the elderly, excellent was observed among 19.8%; and the rest 15.3% had fair/average, while none of the elderly had poor QOL. Determinants significantly associated with QOL with P < 0.05 are age, educational status, professional status, marital status, and behavior of children with them and the elderly with comorbidities. Conclusion: This study shows the association of multiple factors with QOL among the elderly. Factors such as age, educational status, professional status, marital status, and behavior of children with them and the elderly with comorbidities significantly affect the QOL of the elderly. Hence, strengthening the health-care system, increase in level of education, encouraging social interaction, social security systems, and better environmental infrastructure could potentially increase QOL of the elderly population.